2014
DOI: 10.5665/sleep.3312
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes in Neurocognition and Behavior Following Treatment of Sleep Disordered Breathing in School-Aged Children

Abstract: After four years, improvements in SDB are concomitant with improvements in some areas of neurocognition, but not academic ability or behavior in school-aged children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 45 publications
3
60
0
Order By: Relevance
“…15,17,25 Changes in executive function were not significantly different between groups. 17,28 The literature precludes firmer conclusions because relatively few studies have been published comparing tonsillectomy with a nonsurgical intervention for OSDB. Most studies provided little to no clinical outcome data, focusing instead on intermediate outcomes like the AHI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…15,17,25 Changes in executive function were not significantly different between groups. 17,28 The literature precludes firmer conclusions because relatively few studies have been published comparing tonsillectomy with a nonsurgical intervention for OSDB. Most studies provided little to no clinical outcome data, focusing instead on intermediate outcomes like the AHI.…”
Section: Discussionmentioning
confidence: 99%
“…The 5 studies that included children whose OSDB was confirmed with PSG found that AHI scores improved more in children receiving a tonsillectomy than in those who did not undergo surgery (significant group differences in 3 studies). 15,17,25,27,28 Metaanalysis of 3 studies reporting outcomes that could be combined showed a 4.8-point improvement in AHI in children who underwent tonsillectomy compared with no surgery. 17,25,27 Sleep-related quality of life and negative behaviors (eg, anxiety and emotional lability) also improved more among children who had a tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations